ANALISA PENGARUH BATU PORI DAN KERTAS FILTER PADA PENGUJIAN TRIAXIAL TERHADAP LAJU DRAINASE - Widoanindyawati, Vemi; Triwardaya, Triwardaya; Fatmawati, Leily; Parhadi, Parhadi; Suparman, Suparman; Wasino, Wasino (Politeknik Negeri Semarang, 2024)
Soil shear strength testing is a test required for analysis of soil bearing capacity, slope stability, and analysis related to retaining walls. One method of testing soil shear strength is to use a Triaxial tool. The Triaxial test equipment consists of a glass tube which is then filled with water as a pressure cell. Then it is connected to the drainage regulator inside and outside the test object. Failure of the test object is carried out by applying vertical stress to the test object until it collapses. From the Triaxial test, there are several parts that can influence the testing stage process. Among them are the stages of the drainage process, to speed up the rate of drainage, Triaxial test objects require pore stones and filter paper. The use of pro stone and filter paper is based on the type of porosity property. In this research, an analysis of the effectiveness of several types of pore stone will be carried out, including Kaolin dust and types for filter paper, including Whatman No. 54. The placement of pore stone is provided in two variations, including samples with one layer of pore stone and samples with two layers of pore stone. Meanwhile, the sample filter paper is modified by using one layer of filter paper, 2 layers of filter paper, and a drain strip around the sample.